RELATIONSHIP BETWEEN P53 EXPRESSION AND PSA SERUM - Hendri, Ahmad Zulfan; HR, Danarto (Indonesian Journal of Urology, 2012)
Objective: To know the relationship between p53 expression and prostate specific antigen (PSA) serum level in prostate cancer patients. Material & method: Specimens were studied from patients with pathological diagnosis of prostate cancer in Sardjito Hospital Yogyakarta during 2007 to 2008. The p53 expression was measured by immunohistochemical staining. The stains were done in Department of Anatomical Pathology and examined by a pathologist. The relationship between p53 mutated expression and PSA serum level were analyzed with correlation coefficient (rs). Results: There were 29 patients included in this study. The mean age was 66,34 ± 8,15 (50 - 83) years old. The mean PSA serum level was 165,98 ± 269,208 (1,4 – 1051) ng/ml. The mean number of p53 expression was 111,38 ± 94,30 (16 – 396). There was positive correlation between p53 expression and increasing PSA serum level in the prostate cancer patients (rs + 0,497; p = 0,006). Conclusion: P53 expression was positively correlated with increasing PSA serum level.Keywords: Prostate cancer, p53 expression, PSA serum level.